2010
DOI: 10.1128/aac.00870-09
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Mutations in the Connection Domain of Human Immunodeficiency Virus Type 1 Reverse Transcriptase: Assessing the Impact on Nucleoside and Nonnucleoside Reverse Transcriptase Inhibitor Resistance

Abstract: PLoS Med. 4:e335, 2007). In the present study, novel mutations in the connection domain of RT (T369I/V), first identified in patient-derived viruses, were characterized, and their effects on NNRTI and NNRTI susceptibility were determined. Furthermore, the effect of N348I on NRTI and NNRTI resistance was confirmed. HIV-1 with either N348I or T369I/V demonstrated reduced susceptibility to nevirapine (NVP), efavirenz (EFV), delaviridine (DLV), and zidovudine (ZDV) compared to wild-type HIV-1. However, HIV-1 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…However, our in-depth transient kinetics analysis clearly demonstrated a significantly (Ͼ3-fold) decreased catalytic efficiency for p66 N348I /p51 N348I . This reduction in catalytic efficiency is consistent with previous reports by us and others that HIV-1 N348I virus has a reduced replicative capacity (32,33). Hence, N348I imparts a fitness cost to the virus, placing it in the special category of "desirable" mutations that would weaken the virus once acquired.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, our in-depth transient kinetics analysis clearly demonstrated a significantly (Ͼ3-fold) decreased catalytic efficiency for p66 N348I /p51 N348I . This reduction in catalytic efficiency is consistent with previous reports by us and others that HIV-1 N348I virus has a reduced replicative capacity (32,33). Hence, N348I imparts a fitness cost to the virus, placing it in the special category of "desirable" mutations that would weaken the virus once acquired.…”
Section: Discussionsupporting
confidence: 80%
“…These in vitro changes are smaller than those observed in cell-based assays for viruses harboring the same mutation (typically 7-8-fold and up to 27-fold) (31)(32)(33)(34). Such quantitative differences between enzymatic and cell-based estimates of drug resistance are not uncommon.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, recent studies have shown the importance of the Cterminal RT domains (CN and RNH) to drug resistance to NRTI and NNRTI. [23][24][25]30,34,[39][40][41] In this study, mutations in these portions were found in HIV-1B and C infecting patients under virological failure. Despite previous reports that have sporadically documented RT C-terminal mutations in non-B subtypes, 30,35,36 this is the first study specifically assessing differences of mutation occurrence in non-B subtype-specific contexts under the same therapeutic setting.…”
Section: Discussionmentioning
confidence: 96%